Relationship between Mediterranean diet and depression in South Korea: the Korea National Health and Nutrition Examination Survey - Hwang, Yeong-Geon; Pae, Chongwon; Lee, Sang-Hyuk; Yook, Ki-Hwan; Park, Chun Il (Frontiers in Nutrition, 2023)
Background: Several studies have shown that adherence to the Mediterranean diet is associated with a lower risk of depression; however, little is known about the Asian population. This study investigated the relationship between adherence to the Mediterranean diet and depression in a sample of the South Korean population. Methods: In total, 5,849 adults from the 2014 and 2016 Korea National Health and Nutrition Examination Surveys were included in the study. The Mediterranean diet adherence was measured using a modified alternate Mediterranean diet score (mMED) developed to adjust for Korean dietary patterns. The mMED scores using the Food Frequency Questionnaire were divided into four categories (0-2, 3-4, 5-6, and 7-9 points). Subjects with depression were defined as having moderate-to-severe depressive symptoms using the Patient Health Questionnaire-9, with a cutoff value of 10. Logistic regression was used to estimate odds ratios (ORs) and 95% confidence intervals (CIs). A subgroup analysis was performed based on sex. Results: The results of logistic regression analysis indicated that individuals with higher mMED were 42% to 73% less likely to report depression compared to individuals with the lowest mMED [ORs (95% CIs) =0.58 (0.37-0.90), 0.50 (0.31-0.80), 0.27 (0.15-0.47)] after adjusting for sociodemographic and health-related variables. In women, individuals with mMED of 7-9 had 71% lower odds of depression [ORs (95% CIs): 0.29 (0.13-0.64)]. In men, individuals with mMED of 5-9 had 55% [ORs (95% CIs): 0.45 (0.23-0.91)] to 79% [ORs (95% CIs): 0.21 (0.08-0.57)] lower odds of depression.This study suggests that adherence to the Mediterranean diet is inversely associated with depression in both men and women among Korean adults. This study provides evidence that a Mediterranean diet is crucial in preventing depressive symptoms in Asian populations.